Integrating supply chain management with marketing strategies: Enhancing competitive advantage, customer satisfaction, and sustainability - Sutia, Sabar (Journal of Economics and Business Letters, 2022)
This thematic literature review explores the dynamic interplay between supply chain management and marketing strategies, highlighting the crucial role of integrating these functions to achieve enhanced marketing outcomes. Drawing on a wide array of sources, including peer-reviewed journal articles, industry reports, and case studies from the last decade, the review identifies key themes such as the importance of strategic integration, leveraging supply chain capabilities for competitive advantage, and the impact of sustainable supply chain practices on marketing success. The findings underscore that a well-coordinated supply chain not only supports but actively enhances marketing efforts, contributing to superior customer service, differentiation in the marketplace, and a robust commitment to sustainability. Despite the potential benefits, challenges related to supply chain disruptions, cost management, and the adoption of sustainable practices pose significant hurdles. The review concludes with the imperative for businesses to continuously adapt and align their supply chain and marketing strategies to meet evolving consumer demands and environmental standards. Future research directions are suggested to further explore innovative supply chain practices and their impact on marketing outcomes.